Implementation Of Stunting Handling Program Policies At Posyandu Sartika, Kebarepan Village - Sugiartini, Pegi; Hareyan, Enggit; Rahmadhina, Alifa S (Return : Study of Management, Economic and Bussines, 2025)
Stunting is a chronic growth disorder that has an impact on children's physical and cognitive development. The Government of Indonesia stipulates Presidential Regulation Number 72 of 2021 concerning the Acceleration of Stunting Reduction as a national strategy that must be implemented at the village level. This study aims to analyze the implementation of stunting management program policies at Posyandu Sartika, Gamel Village, using George C. Edward III theory, which includes four variables: communication, resources, implementing disposition, and bureaucratic structure. The research uses a qualitative descriptive method with in-depth interview, observation, and documentation techniques. The results showed that the program had been implemented through activities such as weighing, nutrition education, and home visits. However, there are still obstacles such as the limited number of cadres, lack of advanced training, inadequate incentives, and the absence of a written SOP used as a reference for implementation. In conclusion, the implementation of the program has not been optimal in all aspects. Strengthening communication, increasing cadre capacity, providing appropriate incentives, and preparing SOPs are needed to increase the effectiveness of programs at the village level.